Enhanced photoconversion efficiency in cesium-antimony-halide perovskite derivatives by tuning crystallographic dimensionality. (June 2020) - Peng, Yueheng; Li, Fengzhu; Wang, Yan; Li, Yachen; Hoye, Robert L.Z.; Feng, Linrun; Xia, Kai; Pecunia, Vincenzo
Highlights: Structural dimensionality of all-inorganic antimony-based perovskite is tuned. Conversion from 0D to 2D structure is achieved via compositional engineering. Structural conversion enables dramatic external quantum efficiency boost to 62.5%. Improved photoconversion efficiency is associated with charge transport enhancement. Abstract: Lead-based perovskites have reached prominence in optoelectronic and photovoltaic research, yet their toxicity has prompted the search for alternative lead-free compounds. All-inorganic antimony-/bismuth-halide perovskite derivatives have been identified as a promising class of materials. Despite attractive bulk optoelectronic properties, their optoelectronic device performance has been lagging behind. Here we examine one of their most promising embodiments, the all-inorganic cesium-antimony-halide system. Through solution-based halide mixing, we achieve its structural conversion from a zero-dimensional to a layered phase at processing temperatures <150 °C, i.e., much lower than those relied upon in the prior literature (≥230 °C) of all-inorganic cesium-antimony halides. In order to evaluate the technological significance of this finding, we integrate our layered films into a sandwich-type device structure, and characterize their external quantum efficiency and photovoltaic behavior. We find that the structural conversion leads to a considerable enhancement in the optoelectronic device performance. Additionally, photocurrent-power characterization and Hall effect measurements reveal that this performance enhancement is brought about by an improvement in charge carrier transport, which can be exploited due to the unoriented nature of our low-temperature-processed layered films. Such performance boost and mechanistic insight constitute an important step in realizing the full potential of these (and related) compounds for their application in lead-free optoelectronic and photovoltaic devices, e.g., for top-cell in tandem photovoltaics, indoor photovoltaics, and photodetectors. Graphical abstract: Image, graphical abstract